Enhancing Smart City Maturity Through Digital Transformation: A Success Factors Analysis - Listianingsih, Widya; Susanto, Tony Dwi (ISB Atma Luhur, 2025)
Improving smart city maturity through digital transformation is becoming increasingly crucial in facing the challenges of rapid urbanization and the need for more efficient city governance. However, the lack of a unified understanding of key drivers and challenges in this domain has limited the effectiveness of existing strategies. This study aims to explore the role of digital transformation in improving Smart City maturity by identifying key success factors and best practices adopted by cities worldwide. This study used the systematic literature review (SLR) methodology based on the PRISMA framework, which included systematic steps in selecting, collecting, and analyzing relevant literature. The study results reveal six factors influencing Smart City maturity: Information and Communication Technology (ICT) infrastructure, data integration, government policies and strategic planning, stakeholder engagement, environmental sustainability, and innovation and human resource development. Unlike previous studies, this study synthesizes global best practices and success factors, offering actionable insights for policymakers and practitioners to design inclusive, sustainable, and forward- looking digital transformation strategies. Furthermore, the study underscores the need for context-specific research to optimize implementation and drive meaningful progress in diverse urban settings.